Performance Factors in Aloe Vera’s Value Chain as a Green Product - Dinarjad Achmad; Maswadi Maswadi; Umiaty Hamzani (International Journal of Supply Chain Management, 2019)
Market mechanism of agricultural products which is currently applied is based on green economy. Green economy is also run in a farm of Aloe Vera in Pontianak. This study aims to analyze performance factors of Aloe Vera’s value chain as a green product in Pontianak, West Kalimantan. Value chain is analyzed using SEM analysis (Structural Equation Modelling). This research employs multi-stage sampling method and the samples include farmers, traders, consumers, and policy makers (110 respondents). The results showed that coefficient value was positive, indicating that if there is an increase of attention in value chain, farm performance will improve. Activities of value chain’s actors will improve performance as it is related to farming’s input-output management, synergy, and value chain’s integrity. Both indicators are important to ensure value chain’s actors can work to achieve farming performance. Quality performance was examined in terms of diversification and improvement of farming efficiency, increase in added value, increase in farm profitability, and improvement of marketing efficiency.